Petrogenesis of silicic magmas in Iceland through space and time: the isotopic record preserved in zircon and whole rocks - Carley, Tamara L.; Schmitt, Axel Karl (The journal of geology, 2020)
Iceland exemplifies the potential for generation of abundant silicic magma in the absence of mature island arc or preexisting continental crust. Zircon ages (U-Th and U-Pb) and isotope compositions (Hf and O), combined with whole-rock isotope data (Nd, Hf, Pb), provide insight into the petrogenesis and mantle heritage of these silicic magmas. Zircon and whole-rock samples represent the past 15 Ma of Iceland’s geologic evolution, geographic extent (marginal fjordlands to neovolcanic zones), and modern tectonic settings (on-rift, propagating-rift, off-rift). The generation of Icelandic silicic magma has been influenced by hydrothermally altered crust, via assimilation and/or anatexis, throughout Iceland’s history. This is shown by consistently depleted O isotopes in zircon (median δ18O +3.1‰; >98% below +5.3‰), and silicic rocks. Zircon δ18O values appear to have become lower and more diverse since ca. 0.7 Ma (median +1.9‰). This decrease may reflect lower δ18O of meteoric waters involved in hydrothermal alteration during the Pleistocene and/or more volumetrically significant contributions from low δ18O altered crust. Zircon O compositions from historically active volcanoes confirm that the role of altered crust is greater in on-rift than in off-rift settings; diversity in δ18O at volcanoes in propagating rift settings suggests highly variable contributions from altered crust. The silicic record (whole-rock and zircon) exhibits a correlation between geographic position and isotope composition that seems to be independent of local tectonic setting. Silicic samples of all ages collected above 65° N have more radiogenic whole-rock Hf and Nd isotopic compositions, and less radiogenic Pb, than samples collected in southern Iceland; published isotopic data for basalts suggest a similar time-independent latitudinal trend. The persistence of this trend through time suggests that northern Iceland has been underlain by a more depleted mantle source than southern Iceland throughout the island’s history.